2015
DOI: 10.1016/j.protis.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Cu,Zn Superoxide Dismutases from Tetrahymena thermophila: Molecular Evolution and Gene Expression of the First Line of Antioxidant Defenses

Abstract: In the present study, we describe the molecular and functional characterization of two Cu,Zn superoxide dismutase (SOD) genes, named tt-sod1a and tt-sod1b from Tetrahymena thermophila, a free-living ciliated protozoan widely used as model organism in biological research. The cDNAs and the putative amino acid sequences were compared with Cu,Zn SODs from other Alveolata. The primary sequences of T. thermophila Cu,Zn SODs are unusually long if compared to orthologous proteins, but the catalytically important resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 70 publications
2
47
0
Order By: Relevance
“…Virtually all eukaryotic cells contain Cu,Zn SODs [37][38][39][40][41][42], as well as other anti-stress proteins that allow species to withstand environmental stresses of both natural and anthropogenic origin [43][44][45][46][47][48][49][50][51][52][53]. Our results indicated that a gene coding for cytosolic Cu,Zn SOD is present in the genome of the Antarctic icefish C. hamatus and is expressed as active protein in various organs.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Virtually all eukaryotic cells contain Cu,Zn SODs [37][38][39][40][41][42], as well as other anti-stress proteins that allow species to withstand environmental stresses of both natural and anthropogenic origin [43][44][45][46][47][48][49][50][51][52][53]. Our results indicated that a gene coding for cytosolic Cu,Zn SOD is present in the genome of the Antarctic icefish C. hamatus and is expressed as active protein in various organs.…”
Section: Discussionmentioning
confidence: 86%
“…Cytoplasmic foci are known to exist, such as P-bodies or stress granules (SGs), in which these messengers can be stored, undergoing degradation or future translation, respectively [84,85]. This condition is a common feature in organisms that live in stressogenic conditions, but without acute stress [40,86], allowing an extremely rapid response by the tissues toward the sudden onset of acute stress, specifically, a greater biosynthesis of SOD1 in response to increased ROS formation rate. This condition easily occurs in the gills, heart, and skeletal muscle of C. hamatus in relation to its peculiar absence of hemoglobin, which entails chronic hypoxia for the animal and which becomes even more extreme when engaged in locomotor activity, which requires increased oxygen consumption of skeletal muscle and the cardiocirculatory and respiratory systems.…”
Section: Discussionmentioning
confidence: 99%
“…Putative Cu,Zn SOD coding sequences identified by BLAST search in the E. focardii transcriptome were reported in a previous work and named Ef -SOD1a (accession number KF740481) and Ef -SOD1b (accession number KF740482) 29 . Ef -SOD2 (MnSOD, accession number MG575644) is described in this work.…”
Section: Resultsmentioning
confidence: 98%
“…However, while in animals and plants the expression of these genes is generally responsive to environmental change [29,30], in E. nobilii the expression of all four En-MsrB genes has been found to remain substantially unchanged in cells exposed to oxidative and thermal stresses. Consistently with their constitutive expression, the En-MsrB genes have a short 5’ leader non-coding region devoid of cis -active enhancer motifs directly involved in up-regulating the genetic response in stressed organisms, such as the CCCCT ‘stress-response element’ of Saccharomyces cerevisiae [31], the TGAG/CNNNGC ‘antioxidant responsive elements’ of mammalian cells [32], and the TGACNNN ‘half antioxidant response elements’ that are common in other organisms including the ciliate Tetrahymena thermophila [18,33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic relationships were assessed using 122 candidate models, and adopting the ‘Bayesian Information’ (BI) criterion along with the ‘Akaike Information’ criterion used also in the corrected version. The best-fit (clock, no-clock, or relaxed clock) model was selected as previously described [18], by assessing the marginal model likelihoods by means of the stepping-stone method that samples a series of distributions representing different mixtures of the posterior and prior distributions [19]. It was applied to the dataset of the MsrB amino acid sequences using 510,000 generations with a diagnostic frequency of 2,500 in two independent runs for each model.…”
Section: Methodsmentioning
confidence: 99%